SOSIALISASI NORMA-NORMA HUKUM TENTANG KEWAJIBAN PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY BAGI PERUSAHAAN YANG BERGERAK DI BIDANG KEPARIWISATAAN DI SANUR - Dharmawan, N K. Supa sti; Indrawati, A. A. Sri; Rudy, D. G.; Purwanti, N P.; Wiryawan, W.; Sutama, I. B. P. (Buletin Udayana Mengabdi; Vol 12 No 2 (2013): Volume 12 No.2 – September 2013, 2013)
Originally the concept of CSR in developed countries is voluntary (voluntary based). Otherwise, in Indonesia CSR is developed on the basis of legal obligation (mandatory based). Legal norms which expressly stipulate legal obligation for the company to implement Corporate Social Responsibility (CSR) is the Law 40 /2007 on Limited Liability Companies, Government Decree No. 47/ 2012 and Act No. 25/2007 on Investment. According to the Article 74 of Law No. 40/ 2007 as well as the Article 3 Government Decree No. 47/2012, each company running its business activities in the field and / or related to the natural resources is required to carry out social and environmental responsibility including companies engagement in the field of tourism in Sanur Bali. Various CSR activities for the tourism companies in Sanur Bali, besides referring to the legislation are also expected to refer to the concept of Triple Bottom Line (Profit, People, Planet). These are designed to make balance between profit related to People and the Planet for CSR perspective, as well as ISO 26000.